Elucidation of the first committed step in betalain biosynthesis enables the heterologous engineering of betalain pigments in plants. Issue 1 (18th December 2015) - Polturak, Guy; Breitel, Dario; Grossman, Noam; Sarrion‐Perdigones, Alejandro; Weithorn, Efrat; Pliner, Margarita; Orzaez, Diego; Granell, Antonio; Rogachev, Ilana; Aharoni, Asaph
Summary: Betalains are tyrosine‐derived red‐violet and yellow pigments, found in plants only of the Caryophyllales order. Although much progress has been made in recent years in the understanding of the betalain biosynthetic process, many questions remain open with regards to several of the proposed steps in the pathway. Most conspicuous by its absence is the characterization of the first committed step in the pathway, namely the 3‐hydroxylation of tyrosine to form l ‐3, 4‐dihydroxyphenylalanine (l ‐DOPA). We used transcriptome analysis of the betalain‐producing plants red beet ( Beta vulgaris ) and four o'clocks ( Mirabilis jalapa ) to identify a novel, betalain‐related cytochrome P450‐type gene, CYP76AD6, and carried out gene silencing and recombinant expression assays in Nicotiana benthamiana and yeast cells to examine its functionality. l ‐DOPA formation in red beet was found to be redundantly catalyzed by CYP76AD6 together with a known betalain‐related enzyme, CYP76AD1, which was previously thought to only catalyze a succeeding step in the pathway. While CYP76AD1 catalyzes both l ‐DOPA formation and its subsequent conversion to cyclo‐DOPA, CYP76AD6 uniquely exhibits only tyrosine hydroxylase activity. The new findings enabled us to metabolically engineer entirely red‐pigmented tobacco plants through heterologous expression of three genes taking part in the fully decoded betalain biosynthetic pathway. Abstract : See also the Commentary on this article by Schwinn, 210 : 6–9.